Analisis Penerapan Metode Elisitasi untuk Mengukur Pemahaman Grammar Siswa Kelas VIII SMP Terpadu Nurul Islam PEKALONGAN - Hafiz Ghulam; M.Dzikrullah Faza; Mujibul Hakim (STKIP PGRI SITUBONDO, 2025)
Grammar is the essentialone of components in mastering English, serving as the foundation for understanding structure and proper use of the language. However, at the junior high school level, many students struggle to comprehend and accurately apply grammar. Moreover, commonly used evaluation methods, such as written tests, often measure understanding in a limited way and fail to fully capture students' in-depth comprehension of grammar. As an alternative, the elicitation method can be used to assess students' grammar comprehension more effectively. Elicitation is a data collection technique that involves direct interaction with students to explore their knowledge or understanding without providing direct answers. In the context of grammar learning, elicitation can be used to ask students to provide example sentences or explain grammar rules orally, reflecting the extent of their understanding. The study designed and aims to explore the implementation of the elicitation method in measuring the grammar comprehension of eighth- grade students at SMP Terpadu Nurul Islam Pekalongan. By utilizing this method, it is hoped to obtain a more comprehensive picture of students’ understanding of grammar, which may not be revealed through conventional evaluation methods.